2015
DOI: 10.21859/isv.9.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunity against Rubella and Measles Nine Years after Mass Vaccination Program in Babol Medical Students in Iran

Abstract: Background and Aims: Medical students are exposed to various infectious diseases during their clinical training period, including measles and rubella. In Iran, to control the outbreaks of measles and rubella a mass vaccination campaign was conducted on 2003. The present investigation evaluates Immunity to measles and rubella in a group of Babol medical students and determines the prevalence of medical students susceptible to these infections. Materials and Methods: A total of 191 medical students (preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…While a 15% seropositivity rate was reported in one study from Shiraz (24), in other similar study this rate was 74.5% (39). As are presented in Table 5, similar to these variation, also were reported worldwide (28,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Our data in this study are in parallel to that reported in Iranian population and nearly 78% of students as a results of natural infection were seropositive.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While a 15% seropositivity rate was reported in one study from Shiraz (24), in other similar study this rate was 74.5% (39). As are presented in Table 5, similar to these variation, also were reported worldwide (28,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Our data in this study are in parallel to that reported in Iranian population and nearly 78% of students as a results of natural infection were seropositive.…”
Section: Discussionsupporting
confidence: 75%
“…There is no accurate information toward immunity status regarding to these infection among Iranian HSS. However, few studies in this regard were performed (23)(24)(25)(26)(27). The results were varied considerably: 52%(24)-to 88%(26) for measles, 64%(23)-to 76%(24) for mumps, and 96%(23)-to 100%(24) for rubella.…”
Section: Discussionmentioning
confidence: 99%